PEMBERDAYAAN MASYARAKAT MENUJU DESA MANDIRI DAN BERKELANJUTAN DI PADUKUHAN GIRILOYO D.I. YOGYAKARTA MELALUI PROGRAM KERJA KKN XLIII UNIVERSITAS COKROAMINOTO YOGYAKARTA - Rahmawati, Fitri; Devi, Shintia; Muninggarsih, Sofia (Gemi: Jurnal Penelitian dan Pengabdian, 2025)
Giriloyo hamlet has become a place of devotion for the group 09 UCY KKN for 30 days. Based on the analysis of the problem, the focus of attention is the improvement of knowledge, skills and environmental concern. The mechanism for implementing the program is observation, socialization, participation in community empowerment, development of social and cultural programs, DPL guidance, briefing and evaluation. The group work program includes activities such as procurement of stop signs, procurement of garbage cans, Musholah Al Wustho signs, and Ahad Wage service work. The individual work program includes Mushola empowerment activities, procurement of juvenile delinquency posters, support for early childhood education, socialization of saving at an early age, making alley signs, BTA activities, education on the use of plastic waste to make eco-bricks, posyandu support, joint gymnastics, tutoring children, and making hamlet maps. Overall, these programs reflect the joint efforts of KKN students, local communities, and related parties in improving the welfare and development of Giriloyo hamlet. Thus, the results of the above conclusions show that, in general, the KKN program can be said to be successful and smooth, even though the time is more advanced or more backward.